The Effects Of Empty Fruit Bunch Treatments For Straw Mushroom Substrate On Physicochemical Properties Of A Biofertilizer - Sugeng Triyono; Agus Haryanto; Dermiyati Dermiyati; Jamalam Lumbanraja (The University of Lampung, 2019)
This research aims to elaborate characteristics of an organic fertilizer, named as “Organonitrofos”, produced from agricultural wastes supplemented with spent mushroom substrate (SMS) from oil palm empty fruit bunch (EFB). After the experiment of the straw mushroom cultivation was over, the spent EFB was used as one of raw materials for the experiment of Organonitrofos bifertilizer production. Completely Randomized Design was implemented in the experiment of mushroom cultivation. Tereatments consisting of inorganic fertilizer and organic fertilizer factors were applied on the EFB substrate preparation. The inorganic fertilizer and the organic fertilizer each included 3 levels of doses, with 3 replications. After the experiment of the straw mushroom cultivation was over, the spent EFB was used in the experiment of the organic fertilizer production. The spent EFB was mixed with other materials using ratio of 1:1 by volume. The other materials constisted of cattle manure, chicken litter, cocodust, rice husk ash, and MSG industry waste sludge with ratio of 6:1:1:1:1 by volume. After all the materials of every experiemental unis were mixed, fermentation of organic biofertilizer was started with the treatment and the experimental design held the same as those used in the experiment of the mushroom production. The results showed that there was no significantly different among the parameters observed at p<0.05. Winthin 3 month priod of fermentation; however, the screened portion of the compost produced increased to 88.54±1.69% of total weight. C-N ratio (12.80±0.55), organic C (16.11±0.59), total N (1.26±0.59), total P (3.04±0.19), and total K (0.42±0.04) of finished compost met the SNI 19-7030-2004 requirement. Dry weight lost of 2.58±0.59 and ash of 53.96±1.42 content were noted from the finished compost. The organic C content and some other chemical proserties were relatively better than those in previous variants of Organonitrofos. Keywords: Compost, Empty fruit bunch, Organic fertilizer